Elliptical deep anterior lamellar keratoplasty in severe Acanthamoeba keratitis - Haiou Wang; Vishal Jhanji; Cong Ye; Yueping Ren; Qinxiang Zheng; Jinyang Li; Zelin Zhao; Wei Chen (Indian Journal of Ophthalmology, 2023)
Acanthamoeba keratitis (AK) is an intractable infection of the cornea. Penetrating keratoplasty is widely used for the management of severe AK but suffers from complications like graft rejection, endophthalmitis, and glaucoma. Herein, we aimed to describe the surgical technique and the results of elliptical deep anterior lamellar keratoplasty (eDALK) for the management of severe AK. In this retrospective case series, records of consecutive patients with AK poorly responsive to medical treatment who underwent eDALK from January 2012 to May 2020 were reviewed. The largest diameter of infiltration was ≥8 mm and did not involve the endothelium. The recipient bed was made by an elliptical trephine, and big bubble or wet-peeling technique was performed. Postoperative best spectacle-corrected visual acuity, endothelial cell density, corneal topographic data, and complications were evaluated. Thirteen eyes of thirteen patients (eight men and five women, 45.54 ± 11.78 years old) were included in this study. The mean follow-up interval was 21.31 ± 19.59 months (range, 12–82 months). At the last follow-up, the mean best spectacle-corrected visual acuity was 0.35 ± 0.27 logarithm of the minimum angle of resolution. The mean refractive and topographic astigmatism were − 3.21 ± 1.77 and 3.08 ± 1.14 D, respectively. Intraoperative perforation was encountered in one case and double anterior chambers occurred in two cases. One graft developed stromal rejection and one eye developed amoebic recurrence. eDALK can serve as the first-line surgical management of severe AK poorly responsive to medical treatment.